Use of fNIRS to Characterize the Neural Mechanism of Inter-Individual Rhythmic Movement Coordination - Niu, Ruoyu; Yu, Yanglan; Li, Yanan; Liu, Ying (Frontiers in Physiology, 2019)
Background: Inter-individual rhythmic movement coordination plays an important role in daily life, particularly in competitive sports. Behaviorally, it is more challenging to coordinate alternating movements than symmetrical movements. The neural activity underlying these different movement coordination modes remains to be clarified, particularly considering complex inter-individual coordination differences. Methods: To further test the neural basis of inter-individual rhythmic movement coordination, a revised experimental paradigm of inter-individual coordination was adopted. Participants were asked to perform symmetric, alternate, or single movements (swinging the lower part of the leg) in the same rhythm. A multi-channel, continuous wave, functional near-infrared spectral (fNIRS) imaging instrument was used to monitor hemodynamic activity while 40 volunteers (9 male pairs and 11 female pairs) performed the task. Multivariate analyses of variance were conducted to compare mean oxy-hemoglobin concentration ([HbO]) across experimental conditions. Results: A significant three-way interaction (leg-swing condition × ROI × laterality) on mean [HbO] was observed. Post hoc analysis revealed a significant main effect of leg-swing condition only in brain regions of interest (right inferior parietal lobule (IPL)) contralateral to movement execution. Activation in brain regions of interest (right inferior parietal lobule (IPL)) was much stronger in alternate mode compared with symmetric or single modes, and the differences between symmetric and single mode were not statistically significant. This result suggests that the alternate mode of movement coordination was more likely to be supported by the IPL region than the other modes. Conclusion: The present findings provide neural evidence relevant to the theory of self-organization of movement coordination, in which an alternating movement mode appeared to be a more demanding condition than symmetrical movement.